PERBANDINGAN MODEL PEMBELAJARAN CIRC DAN SQ3R TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII SMPN 4 TOMBOLO’PAO - Najmawati Najmawati; Misykat Malik Ibrahim; Wahyuni Ismail (Al-AHYA: Jurnal Pendidikan Biologi, 2019)
This study aims to compare the study result of students of VIII class of SMP Negeri 4 Tombolo’pao’ in biology subject who taught with CIRC model and SQ3R model. This research is a quasi experiment with pretest posttest control group design. The instrument that used in this research was a test of student study result which was administered before and after treatment of those models. The analysis techniques that used were descriptive and inferential statistic. The result shows that the study result of the students who taught with CIRC model was 77,5 and  those who taught with SQ3R was 76,8. Based on inferential analysis, there is no significant difference of student study result between CIRC model and SQ3R model, here  which means Ho was accepted. It could be concluded that both CIRC and SQ3R model had improved study results of VIII class of SMP Negeri 4 Tombolo’pao’ students  in biology subjectKey words : CIRC model, SQ3R and study result